No relationship between myocardial cAMP and positive inotropic effects of convallatoxin - Shi Lin; Wu Chan-qun; Wang Dao-sheng; Liu Shi-zeng; Li Yin-min; Hu Guan-shi; Zhou Zi-qiang; Pan Jian-xin (Acta Pharmacologica Sinica, 2016)
A study of the relationship between positive inotropic effects of convallatoxin and changes in the myocardial intracellular concentrations of Camp was performed. 1. Positive inotropic effects of convallatoxin in 6 anesthetized dogs: the preejection period(PEP), isometric contraction time(ICT) and maximum rate of rise of intraventricular pressure(dp/dtmax) were measured from simultaneous recordings of the electrocardiogram, phonocardiogram, aortic pressure and a chest pneumograph employing a multichannel polygram system. The maximal effects of convallatoxin on the elevation of myocardial contractility occurred in 45 min after an iv of 0.03 mg/kg. At this time, the PEP was significantly reduced from 91±5 ms to 78±4 ms, the IVCT was reduced from 49±4 ms to 37±3 ms, while the dp/dtmax was reapidly increased to a maximum of 124% of the control level. 2. Effects of convallatoxin on myocardial intracellular cAMP concentrations in guinea pig and rat hearts: the hearts of 80 guinea pigs were excised and Camp was measured in 30 min following the injections of covallatoxin at therapeutic doses (0.05, 0.1 and 0.15 mg/kg) or a toxic dose (0.3 mg/kg). The mean values of myocardial Camp concentrations showed no significant deviations from those of control guinea pigs. Similar results were obtained on 18 rats. 3. Effects of convallatoxin on plasma cAMP of anesthetized dogs: forty-five min after the iv of convallatoxin 0.03 mg/kg, a significant increase of Camp concentration in peripheral blood from 31±5 to 41±4 pmol/mL (n=6) was revealed. When the dose of convallatoxin reached 0.06 mg/kg, the blood plasma cAMP concentration was elevated from 38±3 to 73±11 pmol/mL(n=8) in 30 min following the injection. From the above results, it may be concluded that the augmentation of myocardial contractility induced by convallatoxin was not mediated via myocardial intracellular cAMP.